Relative intensities and compositions of multifactorial peak kinematic and mechanical demands in elite youth soccer - Yousefian, F.; Zafar, A.; Nakamura, F. Y.; Menezes, P.; Brito, J.; Travassos, B. (Frontiers in Sports and Active Living, 2025)
Background: Characterizing the most demanding passages (MDP) of physical activity during soccer competition is essential for optimizing training prescription and player monitoring. However, research investigating kinematic and mechanical MDP using a multifactorial criterion variable approach in elite youth soccer players remains limited. This study examined the relative intensities and compositional structure of multifactorial kinematic and mechanical MDP across different durations in an elite youth international tournament.